Systematic review and meta-analysis of factors associated with caregiver burden in dementia in Latin America and the Caribbean (2025)
This systematic review and meta-analysis examined 33 studies (N = 2667) conducted in Latin America and the Caribbean (LAC) to identify the clinical and psychosocial factors associated with caregiver burden in dementia. Results showed that neuropsychiatric symptoms, caregiver depression, patient depression, and the caregiver’s perception of patient quality of life (QoL) were consistently linked to greater burden. In contrast, patient functionality and cognition were not significantly associated unless moderated by caregiver age or sex. Caregiver education emerged as a key moderator in several associations, often intensifying perceived burden. These findings highlight the need for culturally sensitive, emotionally focused interventions tailored to caregivers’ contexts in the region.